2015
DOI: 10.1515/pjvs-2015-0113
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of using serum hialuronic acid concentrations in the diagnosis of canine liver fibrosis

Abstract: There are multiple dynamic changes associated with the metabolism of the extracellular matrix (ECM) which occur in the course of liver fibrosis. Therefore, the evaluation of parameters reflecting the deposition of ECM, the activity of myofibroblasts and the synthesis and degradation of collagen may aid in the diagnosis of liver fibrosis. Hyaluronic acid is considered to be a marker of ECM deposition. It is a glycosaminoglycan synthesized by hepatic stellate cells and degraded by hepatic sinusoidal endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Our study, as well as previously reported studies of liver biomarkers in dogs have enrolled relatively few dogs with cirrhosis. This is an important limitation because many biomarker studies in humans focus on distinguishing cirrhotic from non‐cirrhotic patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our study, as well as previously reported studies of liver biomarkers in dogs have enrolled relatively few dogs with cirrhosis. This is an important limitation because many biomarker studies in humans focus on distinguishing cirrhotic from non‐cirrhotic patients.…”
Section: Discussionmentioning
confidence: 85%
“…Serum concentrations of hyaluronic acid, which is produced by hepatic stellate cells, were significantly increased in dogs with cirrhosis, with only modest overlap in dogs without cirrhosis or with non‐hepatic diseases . In another study, serum hyaluronic acid concentrations were distinctly higher in dogs with stage 4 fibrosis, although statistical comparisons were not made . The same research group also reported significantly higher serum concentrations of type III procollagen aminopeptide (PIIINP) and a fragment of type IV collagen (PIVNP) in dogs with advanced liver fibrosis .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As mentioned before, LSEC regulate HSC activation via an alteration of the balance of vasodilators/vasoconstrictors molecules. LSEC also contribute to HSC activation through additional ways: secreting fibronectin EIIIA [161,162], TGF-β and PDGF or activating signaling pathways such as Hh or Wntβcatenin, which can activate HSC in both a paracrine and an autocrine manner [72,[74][75][76][163][164][165][166][167][168][169][170].…”
Section: Loss Of Anti-fibrotic Capacitiesmentioning
confidence: 99%
“…Some of these serum markers have been evaluated in dogs. Serum hyaluronic acid concentration is increased in dogs with hepatic disease, especially cirrhosis, and therefore holds some promise as a biomarker . Serum concentrations of TGFβ‐1, the 7S fragment of type IV collagen, and procollagen type III N‐terminal peptide also have been found to be increased in dogs with hepatic fibrosis.…”
Section: Diagnosis Of Hepatic Fibrosismentioning
confidence: 99%